Atrial myxoma: tumour or trauma?. Issue 5 (May 1992) - Nolan, J; Carder, P J; Bloomfield, P
Abstract : A mass lesion developed in the right atrium at the site of a trans-septal puncture after percutaneous balloon dilatation of the mitral valve in a man aged 74. The lesion had the pathological appearance of an atrial myxoma and seemed to have developed after trauma to the intra-atrial septum. This case suggests that at least some atrial myxomas are reactive rather than neoplastic in origin.